Determination of metals’ migration from unplastified poly(vinyl chloride) exposed to accelerated ageing - Borowska, A.; Sterzyński, T.; Pokora, M. (Polimery, 2021)
14 blends of unplastified poly(vinyl chloride) (PVC-U) containing pigments, stabilizing systems and fillers were prepared (Table 1, 2) and then exposed to accelerated ageing by UV radiation in a chamber. The migration of metals: Fe, Pb, Ca, Mn, Mg, Al, Zn, Ti, Si and Zr from the sample surface layer to model liquid was determined by inductively coupled plasma atomic emission spectroscopy (ICP). The difference between the migration value of initial material and of aged one was treated as a measure of PVC-U degradation degree (Fig. 1-4). Additionally the thermal stability of the samples before and after UV irradiation was studied (Fig. 6). The cross-section of samples (Fig. 5) were visually evaluated.